Mitigating the impact of cultural diversity on the innovation process in the private sector in Dubai - HAJI, HASSAN (2017)
Thomas, (1999), defined cultural diversity to encompass the sum total of human beliefs, norms, virtues, and various activities that are regarded to be part and parcel of the community. Cultural diversity involves different practices that form a functional unit among societies in a certain area. The author further noted that cultural diversity has formed a paramount issue in business arena that need to be investigated to pave a clear way in order to accommodate people from various backgrounds. Often, globalization has been the reason behind a variety of innovation in business, therefore, people of different races, age, lifestyles, religions and ethnic groups in workforce. To ensure that people cooperate, carry out their activities and responsibilities effectively and efficient in the world of business it is necessary to understand their likes and dislikes. According to Ely and Thomas (2001), for easy running and management of organization’s operations and activities, it is paramount to ensure that all workers have clear mental and physical images of their co-workers and this provides healthy environment from which they can work harmoniously and in a coordinated manner. The authors further noted that in workplace, employees have different abilities, capabilities and talents, therefore, to maximise productivity, workers’ different cultures must be embrace. Their research further identified that diversity is not a success by itself rather it can result to numerous merits within a business organization, for instance it improves the innovativeness of the workers, managers, practitioners and that of the company as well (Ely, & Thomas, 2001). Through the statistical data analysis, it was noted that, managers are not in any way entangled in to check or control cultural diversity and this may further pose a slowdown or decline the organization’s productivity. Cultural diversity can result to negative effects to creativity and innovativeness depending on the way workers handle people from different races, religions, ethnic groups and lifestyles among many others. (Hawless, 2013). The main purpose of the present study is to analyse and investigate various methods of mitigating the negative effects that come as a result of cultural diversity on innovation and creativity process in the private-operated business organizations, specifically he construction projects in Dubai. The economy in the Middle East countries has been on the rise in the recent years, and therefore, the management in various departments and government sector have been in search for labour from different parts of the world, specifically in developing countries. The workforce therefore is comprised of people with different backgrounds and hence an understanding for the variety of cultures is important for managers and entrepreneurs in private sectors as noted by the write (2016). The Writer (2016) f noted that fall in oil prices has resulted to people chasing other opportunities, and this has led to a tremendous improvement in private investments, particularly in the sectors of travel, project construction and tourism. The writer (2016), notes that the oil product has been on the decline, these has led to less aggressiveness in the field and hence fetching low prices. It is true that the aim of any business is to make profit, with decreased profit in the sector many entrepreneurs have discovered other investment schemes which has resulted to more demand of the workforce. As a consequence of the increased demands and bearing in mind that Dubai cannot provide the demand, importation of the labour force has formed a permanent solution to this dilemma. The workers move from all corners of the world with different beliefs, cultures, norms, virtues and lifestyle, therefore accommodation of such can be challenging because people have different ways of carrying out their activities and therefore, this formed the basis of the present study on checking the impacts of cultural diversity to the process of innovation in the private-operated sector in Dubai. The rise in the workforce comprising of individuals of different origins has made it crucial to investigate and examine various factors that impact on the project, particularly the cultural diversity and how to mitigate the effects that come along. Creativity and innovation in various organization form basis of improving the goods and services that are offered and therefore, according to Ozgen (2014), a research that is inclined or construed towards establishing the impacts and consequently providing solution or insights on way forward on the subject is quite paramount. The author further asserts that, a research on the cultural diversity if done objectively has positive impacts to the economy of any given country. According to Patrick (2012), cultural diversity has negative impacts on the organization such as slowing down the activities and operations, as well acting as a stumbling block to the organization’s success. Patrick (2012) conducted a research to investigate and examine the impacts of cultural diversity, through the review of the literature; the author noted that some sections indicated mitigating actions and strategies that can be employed in verge to reduce the negativity that cultural diversity has on innovation process. The author noted that, several strategies such as training the employees on the importance of embracing people’s culture and the undermining factors that go long way against cultural diversity